Engineering Purcell factor anisotropy for dark and bright excitons in two dimensional semiconductors. (2nd June 2022) - Eswaramoorthy, Lekshmi; Mokkapati, Sudha; Kumar, Anshuman
Abstract: Tightly bound dark excitons in atomically thin semiconductors can be used for various optoelectronic applications including light storage and quantum communication. Their optical accessibility is however limited due to their out-of-plane transition dipole moment. We thus propose to strengthen the coupling of dark excitons in two dimensional materials with out-of-plane resonant modes of a cavity at room temperature, by engineering the anisotropy in the Purcell factor. A silica micro-disk characterised by high confinement of light in small modal volume, high Q -factor and free spectral range is used to couple to the excitons in monolayer transition metal dichalcogenides (TMDCs). We show numerically that the tapering of sidewalls of the micro-disk is an extremely versatile route for achieving the selective coupling of whispering gallery modes to light emitted from out-of-plane dipoles to the detriment of that from in-plane ones for four representative monolayer TMDCs.